Effect of Ankle Position on Tibiotalar Motion With Screw Fixation of the Distal Tibiofibular Syndesmosis in a Fracture Model. (June 2018) - Pallis, Mark P.; Pressman, David N.; Heida, Kenneth; Nicholson, Tyler; Ishikawa, Susan
Background: Anatomic reduction and fixation of the syndesmosis in traumatic injuries is paramount in restoring function of the tibiotalar joint. While overcompression is a potential error, recent work has called into question whether ankle position during fixation really matters in this regard. Our study aimed to corroborate more recent findings using a fracture model that, to our knowledge, has not been previously tested. Methods: Twenty cadaver leg specimens were obtained and prepared. Each was tested for tibiotalar motion under various conditions: intact syndesmosis, intact syndesmosis with lag screw compression, pronation external rotation type 4 (PER-4) ankle fracture with syndesmotic disruption, and single-screw syndesmotic fixation followed by plate and screw fracture and syndesmotic screw fixation. In each situation, the ankle was held in alternating plantarflexion and dorsiflexion when inserting the syndesmotic screw with the subsequent amount of maximal dorsiflexion being recorded following hand-tight lag screw fixation. Results: While ankle range of motion increased significantly with creation of the PER-4 injury, under no condition was there a statistically significant change in maximal dorsiflexion angle. Conclusion: Ankle position during distal tibiofibular syndesmosis fixation did not limit dorsiflexion of the ankle joint. Clinical Relevance: Our findings suggest that maximal dorsiflexion during syndesmotic screw fixation may not be necessary.